A Sequential Explanatory Investigation in using ICTs on Arabic Language and Islamic Values Education: Teacher-Students Perspective - Muhammad Ikhlas; Kuswanto Kuswanto; Sri Ramdayeni Sakunti; M. Rivanda Debi; Leila M. Collantes (Universitas Muhammadiyah Surakarta, 2021)
This study aims to see the extent of the application of ICT in the ALIVE program at Munoz Central School, as well as its effectiveness in the use of ICT. Furthermore, this study uses a mixed methods research design with a sequential explanatory approach. The sample of this study were students who took the ALIVE pro-gram at Munoz Central School. Quantitative and qualitative results indicate that the implementation of ICT in the ALIVE program is already good, it can be seen from the utilization of some ICT features performed by the teacher, as well as the effectiveness of ICT, where the presence of ICT in ALIVE learning is very helpful in the learning process. This certainly indicates that the use of ICT in the ALIVE program at Munoz Central School is good but needs improving that the learning that is carried out is even more increasing. With the increased use and facilities of the ICT in the ALIVE program, of course, it will make learning much better in the future and requires the attention of various related stakeholders.